The differences in diet quality and physical activity for COVID-19 survivors and non-survivors in Semarang City - Novitasari Dwi Ajeng; Fillah Fithra Dieny; Rachma Purwanti; Ani Margawati; Nariswari Prajna Paramitha (AcTion: Aceh Nutrition Journal, 2024)
The COVID-19 pandemic triggered lifestyle changes, namely diet quality and physical activity, which showed improvements in COVID-19 survivors. This study aimed to analyze the differences in diet quality and physical activity among COVID-19 survivors and non-survivors in the city of Semarang between March and April 2022. The study design was cross-sectional, with as many as 100 Semarang City residents aged 22-45 years (50 survivors and 50 non-survivors of COVID-19) using a purposive sampling technique. Semi-quantitative food frequency questionnaire (SQ-FFQ) interview data were collected, followed by diet quality assessment using the Diet Quality Index-International (DQI-I). Physical activity data were collected using the International Physical Activity Questionnaire-Short Form (IPAQ-SF). Data were analyzed using the Mann-Whitney and Spearman's methods. The diet quality of the two groups showed a difference (p=0,012), with the diet quality of the survivor group being better. Variations in dietary quality components showed significant differences (p<0,001), including the subcomponents of overall (p=0,005) and protein (p<0,001). Physical activity in both groups showed no significant difference (p=0,639), including heavy, moderate, and walking activities. There was a significant difference in sedentary activity between the two groups (p=0,035). Conclusion: The dietary quality of the two groups showed differences, the majority of which was better in the COVID-19 survivor group. Physical activity in both groups showed no difference, but sedentary activity differed between the two groups